Avaliação dos revestimentos de zinco com incorporação de partículas poliméricas - Tomachuk, C. (2012)
In the last 30 years, zinc plating had remarkable development due to the increasing demand for coatings with better corrosion resistance from the automotive industry. Hexavalent chromium compounds have been used to create conversion layers on zinc providing better anticorrosive protection as well as anchorage properties to painting systems. However, new and more severe environmental regulations impose elimination of these compounds on electrolytes for electroplating and passivation baths and its replacement by environmentally friendly products. In this work, the surface characteristics and electrochemical behavior of a zinc coating added with silicate nanoparticles included in a polymeric matrix were investigated with the aim of evaluating its effectiveness against corrosion. Then, to improve the coating protective properties a barrier waterborne polyurethane film was applied. The characteristics of the dried polymer film (such as adhesion metal/polymer, porosity, rusting degrees and blistering) were investigated using standardized tests while the corrosion resistance was evaluated by means of electrochemical techniques in solution 0.05 mol/L NaCl. The incorporation of silicate nanoparticles include in a polymeric matrix in the zinc coating provided good adhesion of the coating system without the need of applying an application of the passivation layer on the zinc coating.